Inter- and intra-laboratory comparison of a multibiodosimetric approach to triage in a simulated, large scale radiation emergency. (February 2014) - Ainsbury, Elizabeth A.; Al-Hafidh, Jenna; Bajinskis, Ainars; Barnard, Stephen; Barquinero, Joan Francesc; Beinke, Christina; de Gelder, Virginie; Gregoire, Eric; Jaworska, Alicja; Lindholm, Carita; Lloyd, David; Moquet, Jayne; et al.
Abstract Purpose: The European Union's Seventh Framework Programme-funded project 'Multi-disciplinary biodosimetric tools to manage high scale radiological casualties' (MULTIBIODOSE) has developed a multiparametric approach to radiation biodosimetry, with a particular emphasis on triage of large numbers of potentially exposed individuals following accidental exposures. In November 2012, an emergency exercise took place which tested the capabilities of the MULTIBIODOSE project partners. The exercise described here had a dual purpose: Intercomparison of (i) three biodosimetric assays, and (ii) the capabilities of the seven laboratories, with regards to provision of triage status for suspected radiation exposed individuals. Materials and methods: Three biological dosimetry tools – the dicentric, micronucleus and gamma-H2AX (the phosphorylated form of member X of histone H2A, in response to DNA double-strand breaks) foci assays – were tested, in addition to provision of the triage status results (low exposure: < 1 Gy; medium exposure: 1–2 Gy; high exposure: > 2 Gy) by the MULTIBIODOSE software. The exercise was run in two modes: An initial triage categorisation of samples (based on the first dose estimates for each assay received from each laboratory) followed by collation of the full set of estimated doses (all the results from all modes of each assay carried out by the participating laboratories) calculated using as many modes of operation as possible of the different assays developed during the project. Simulated acute whole body and partial body exposures were included. Results: The results of the initial triage categorisation and the full comparison of assays and methods within and between laboratories are presented here. Conclusions: The data demonstrate that the MULTIBIODOSE approach of applying multiparametric tools to radiation emergencies is valid and effective.